Psychosocial work characteristics and self rated health in four post-communist countries. Issue 9 (1st September 2001) - Pikhart, H; Bobak, M; Siegrist, J; Pajak, A; Rywik, S; Kyshegyi, J; Gostautas, A; Skodova, Z; Marmot, M
Abstract : STUDY OBJECTIVES: To examine whether psychosocial factors at work are related to self rated health in post-communist countries. DESIGN AND SETTINGS: Random samples of men and women in five communities in four countries were sent a postal questionnaire (Poland, Czech Republic and Lithuania) or were invited to an interview (Hungary). Working subjects (n=3941) reported their self rated health in the past 12 months (5 point scale), their socioeconomic circumstances, perceived control over life, and the following aspects of the psychosocial work environment: job control, job demand, job variety, social support, and effort and reward at work (to calculate a ratio of effort/reward imbalance). As the results did not differ by country, pooled analyses were performed. Odds ratios of poor or very poor health ("poor health") were estimated for a 1 SD increase in the scores of work related factors. MAIN RESULTS: The overall prevalence of poor health was 6% in men and 7% in women. After controlling for age, sex and community, all work related factors were associated with poor health (p<0.05). After further adjustment for perceived control, only two work related factors remained associated with poor health; the odds ratios (95% confidence intervals) for 1 SD increase in the effort/reward ratio (log transformed) and job variety were 1.51 (1.29, 1.78) and 0.82 (0.73, 1.00), respectively. Further adjustment for all work related factors did not change these estimates. There were no interactions between individual work related factors, but the effects of job control and social support at work differed by marital status, and the odds ratio of job demand increased with increasing education. CONCLUSIONS: The continuous measure of effort/reward imbalance at work was a powerful determinant of self rated health in these post-communist populations. Although the cross sectional design does not allow firm conclusions as to causality, this study suggests that the effect of the psychosocial work environment is not confined to Western populations.